From Quantum Paraelectric/Ferroelectric Perovskite Oxides to High Temperature Superconducting Copper Oxides -- In Honor of Professor K.A. Müller for His Lifework - Bussmann-Holder, Annette; Keller, Hugo; Bianconi, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
With this book, we wish to honor the lifework of K. Alex Müller and present him with this book on the occasion of his 94th birthday. We are convinced that he will very much enjoy reading it. We would like to thank all contributors to this book, who addressed topics complementary and related to his work. The articles of the book represent the efforts in solid state physics - spanning more than 60 years - which have been groundbreaking in scientific and applied sciences. Many of the current hot topics are derived from this earlier work which has pioneered the way toward new experimental tools and/or refined techniques. From this point of view, the book presents, on one hand, a historical review and, on the other hand, a directory of possible future research.